Histone variants take center stage in shaping the epigenome. (June 2021) - Borg, Michael; Jiang, Danhua; Berger, Frédéric
Highlights: The combination of histone variants greatly expands nucleosome diversity. H2A and H2B variants occupy distinct chromatin landscapes. Histone H3.1 controls epigenetic inheritance across the cell cycle. Replacement and specialized H3 variants mediate epigenetic reprogramming. Abstract : The dynamic properties of the nucleosome are central to genomic activity. Variants of the core histones that form the nucleosome play a pivotal role in modulating nucleosome structure and function. Despite often small differences in sequence, histone variants display remarkable diversity in genomic deposition and post-translational modification. Here, we summarize the roles played by histone variants in the establishment, maintenance and reprogramming of plant chromatin landscapes, with a focus on histone H3 variants. Deposition of replicative H3.1 during DNA replication controls epigenetic inheritance, while local replacement of H3.1 with H3.3 marks cells undergoing terminal differentiation. Deposition of specialized H3 variants in specific cell types is emerging as a novel mechanism of selective epigenetic reprogramming during the plant life cycle.